2017
DOI: 10.2147/opth.s134570
|View full text |Cite
|
Sign up to set email alerts
|

Ocular lubricant use in medically and surgically treated glaucoma: a retrospective longitudinal analysis

Abstract: BackgroundChronic use of intraocular pressure-lowering medications is associated with ocular surface disease (OSD). In this study, we assess the incidence of topical lubricant use as a surrogate marker for underlying OSD, in medically and surgically treated glaucoma patients.MethodsRetrospective chart review was performed for newly diagnosed glaucoma patients who were started on topical medications in 2007 and followed up over a 5-year period. Primary outcome measure was the incidence of topical lubricant use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…One 5-year retrospective study of 500 patients with glaucoma showed that 54% used artificial tears. 69 One randomized double-masked, controlled study compared two types of preservative-free artificial tears: sodium hyaluronate and hydroxypropyl methylcellulose (HPMC)/dextran. 70 HPMC is a conventional ingredient of artificial tears, while sodium hyaluronate is a naturally lubricating viscoelastic solution that has demonstrated a reduction in the ocular toxicity of BAK with in vitro studies.…”
Section: Treatment Of Ocular Surface Disease In Patients On Topical G...mentioning
confidence: 99%
“…One 5-year retrospective study of 500 patients with glaucoma showed that 54% used artificial tears. 69 One randomized double-masked, controlled study compared two types of preservative-free artificial tears: sodium hyaluronate and hydroxypropyl methylcellulose (HPMC)/dextran. 70 HPMC is a conventional ingredient of artificial tears, while sodium hyaluronate is a naturally lubricating viscoelastic solution that has demonstrated a reduction in the ocular toxicity of BAK with in vitro studies.…”
Section: Treatment Of Ocular Surface Disease In Patients On Topical G...mentioning
confidence: 99%
“…[60][61][62] It has been largely demonstrated that the number of glaucoma patients suffering from dry eye increases with the number of medications used and with disease duration. 63 In this particular population, the use of preservative-free medications and tear supple-ment [64][65][66][67] is very useful to reduce dry eye symptoms. Particularly, cross-linked HA, for its stability and persistence over the ocular surface, may represent a valid alternative.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…При этом каждая дополнительная капля гипотензивного средства статистически достоверно (примерно на четверть) повышает так называемый индекс патологии глазной поверхности (Ocular Surface Disease Index, OSDI). Особенно страдают пациенты с фоновым синдромом сухого глаза [3,4].…”
Section: Introductionunclassified